Xenohormone transactivities are inversely associated to serum POPs in Inuit - Bonefeld-Jorgensen Eva C; Deutch Bente; Hjelmborg Philip S; Ghisari Mandana; Krüger Tanja (BMC, 2008)
Abstract Background The persistent organic pollutants (POPs) are highly lipophilic and resistant to biodegradation and found in e.g. seafood and marine mammals. Greenlandic Inuit have high intake of marine food and thus high POP burden that varies according to local conditions and dietary preference. We do for the very first time report the serum POP related non-steroidal xenohormone activity of Inuit across Greenland. The aims were 1) to determine the integrated xenohormone bioactivities as an exposure biomarker of the actual lipophilic serum POP mixture measuring the effect on estrogen (ER) and androgen receptor (AR) transactivity in citizens from different Greenlandic districts and 2) to evaluate associations to serum POP markers (14 PCBs and 10 pesticides) and lifestyle characteristics. Methods Serum samples from 121 men and 119 women from Nuuk, Sisimiut and Qaanaaq were extracted using SPE-HPLC fractionation to obtain the serum POP fraction free of endogenous hormones. The serum POP fraction was used for determination of xenohormone transactivity using ER and AR reporter gene assays. Results In overall, the xenohormone transactivities differed between districts as well as between the genders. Associations between the transactivities and age, n-3/n-6 and smoker years were observed. The xenoestrogenic and xenoandrogenic transactivities correlated negatively to the POPs for the combined female and male data, respectively. Conclusion The non-steroidal xenohormone transactivities can be used as an integrated biomarker of POP exposure and lifestyle characteristics. The actual serum POP mixtures antagonized the age adjusted sex hormone receptor functions. Comparison of different study populations requires in addition to age inclusion of diet and lifestyle factors.